A participação societária dos fundos de pensão nas empresas listadas na BM&FBOVESPA: fatores explicativos da atração de investimentos - Mangoni, Luiz Alberto (Universidade do Vale do Rio dos Sinos, 2015)
The aim of this study was to analyze the characteristics of the companies listed on the BM&FBOVESPA that attract investments of Brazilian pension funds in the period 2005 to 2013. Above all, the organizations should provide positive results to its shareholders as profit or asset growth. Based on this statement and added to studies that evidence the relation between investment attraction and pension funds was developed this research. For analysis, descriptive data and linear regression were used. Positive statistical relations were found between the percentage of ownership interest of the pension funds and the size of companies, as well as adherence of this companies to one of the differentiated levels of corporate governance. A no statistical relation was observed between spending on R&D and pension funds’ investments. The sample consists of companies which carry on their shareholding structure at least one pension fund between the years 2005 and 2013. This research could contribute to future studies regarding pension funds’ investments and to understand the behavior of these companies on the use of its resources.
Keywords: Fundos de pensão; Decisões de investimento; Atração de investimentos; Mercado acionário; Pension funds; Investment decisions; Investment attraction; Stock market; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis